1999
DOI: 10.1038/sj.mp.4000494
|View full text |Cite
|
Sign up to set email alerts
|

Anti-bipolar therapy: mechanism of action of lithium

Abstract: This review introduces the concepts that multiple actions of lithium are critical for its therapeutic effect, and that these complex effects stabilize neuronal activities, support neural plasticity, and provide neuroprotection. Three interacting systems appear most critical. (i) Modulation of neurotransmitters by lithium likely readjusts balances between excitatory and inhibitory activities, and decreased glutamatergic activity may contribute to neuroprotection.(ii) Lithium modulates signals impacting on the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
269
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 333 publications
(273 citation statements)
references
References 93 publications
(114 reference statements)
3
269
0
1
Order By: Relevance
“…The phosphorylation of cellular signaling proteins has been implicated in the pathophysiology of numerous neuropsychiatric diseases Jope, 1999;Konradi and Heckers, 2001;Lenox and Hahn, 2000;Maccioni et al, 2001). Indeed, the phosphorylated form of a protein is clearly of major biological interest; it often affects the function and/or subcellular distribution of enzymes, receptors, neurotransmitter transporters, ion channels, and transcription factors.…”
Section: Introductionmentioning
confidence: 99%
“…The phosphorylation of cellular signaling proteins has been implicated in the pathophysiology of numerous neuropsychiatric diseases Jope, 1999;Konradi and Heckers, 2001;Lenox and Hahn, 2000;Maccioni et al, 2001). Indeed, the phosphorylated form of a protein is clearly of major biological interest; it often affects the function and/or subcellular distribution of enzymes, receptors, neurotransmitter transporters, ion channels, and transcription factors.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the delayed onset of therapeutic action of lithium has led to the hypothesis that regulation of gene expression may be important for its mood stabilizing effects (Jope 1999;Li et al 2000). In line with this hypothesis, several studies have demonstrated that chronic lithium treatment alters the expression of an array of genes, including G protein ␣ -subunits, adenylyl cyclase subtypes, neuropeptides (reviewed in Jope 1999;Li et al 2000;Manji and Lenox 1999) NO .…”
Section: The Latency In Onset Of Antimanic and Mood Stabilizing Effecmentioning
confidence: 99%
“…ever, significant progress has been made over the past decade with cumulative evidence indicating that modulation of postreceptor signaling mechanisms in critical regions of the brain may be essential to the mood stabilizing properties of this agent (reviewed in Jope 1999;Li et al 2000;Manji and Lenox 1999).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Further evidence for the involvement of PKC in bipolar disorders is derived from observations that lithium exerts significant effects on PKC in a number of cell systems, including central nervous system (CNS) (Manji et al 1993(Manji et al , 1995Manji and Lenox 1999). Therefore, it has been suggested by some investigators that PKC may be an important target for the action of mood stabilizers, such as lithium and valproate (Lenox and Manji 1998;Ikonomov and Manji 1999;Jope 1999).Although activation of PKC causes a variety of physiological responses, the steps involved between the activation of PKC and subsequent physiological responses are not known. One approach to examine the molecular steps between the activation of PKC and subsequent physiological responses is study of the substrates for PKC, which may help in understanding the downstream events.…”
mentioning
confidence: 99%